Study of Educational Thematic Data in the Indonesian Border Region in Nusa Tenggara Timur Province - Kennedy, Posma Sariguna Johnson; Tobing, Suzanna Josephine L.; Toruan, Rutman L. (American Journal of Social Sciences and Humanities, 2019)
This paper wants to see the problem of education in the Indonesian border region in the Nusa Tenggara Timur or East Nusa Tenggara Province (NTT). The research method used by examining some literature and using quantitative descriptions with data sources is secondary data. The data obtained came from the Ministry of National Development Planning/Bappenas. The data taken is devoted to the results of the analytical method with a "thematic" approach. The growth of education services in NTT has increased as an investment in education by the government. However, the average education rating in NTT was the fourth lowest in Indonesia. The districts in the border areas that have better conditions as the third priority are Timor Tengah Utara, Kupang, and Belu Regencies, whereas communities in the border areas as the second priority are Alor and Malacca Regencies. The primary problem is the sustainability problem, the willingness of students to continue their education in each generation. Then there is a problem of stability, where border areas in NTT were prone to disasters. Also availability problem, the availability of teachers and school infrastructure and the number of students who continue their education.